2016
DOI: 10.1177/0022042616661836
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed-Method Analysis of Reports on 100 Cases of Improper Prescribing of Controlled Substances

Abstract: Improper prescribing of controlled substances contributes to opioid addictions and deaths by overdose. Studies conducted to-date have largely lacked a theoretical framework and ignored the interaction of individual with environmental factors. We conducted a mixed-method analysis of published reports on 100 cases that occurred in the United States. An average of 17 reports (e.g., from medical boards) per case were coded for 38 dichotomous variables describing the physician, setting, patients, and investigation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 41 publications
(56 reference statements)
0
20
0
Order By: Relevance
“…We coded in two rounds. Most variables were deductive in that they were based on our systematic literature reviews and past research projects on cases of professional breaches [ 14 , 15 , 34 , 35 ]. However, some variables—such as specific fraud charges, relationships to industry, and the dollar amounts billed—were inductive, arising from the process of coding the cases.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We coded in two rounds. Most variables were deductive in that they were based on our systematic literature reviews and past research projects on cases of professional breaches [ 14 , 15 , 34 , 35 ]. However, some variables—such as specific fraud charges, relationships to industry, and the dollar amounts billed—were inductive, arising from the process of coding the cases.…”
Section: Methodsmentioning
confidence: 99%
“…The study reported in this paper is part of a larger project to understand causal factors associated with significant professional breaches in medicine such as running an opioid “pill mill,” [ 14 ] inappropriately touching patients during exams, [ 15 ] and performing unnecessary surgeries for profit. We have focused on high-profile cases of professional breaches that directly cause significant harm to patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Current work by DuBois and colleagues on misprescribing of controlled substances (primarily opioids) found similar patterns. 51 Rather than studying physician demographics, Rich and Webster looked at underlying behavior patterns by analyzing medical records in malpractice opioid overdose cases from 2005 to 2009. 52 They attributed the cause of overdose to physician error in seventy-five percent of the cases.…”
Section: Defining Misprescribing Amidst Incomplete Data and An Inmentioning
confidence: 99%
“…There is very little evidence to suggest, however, that mental disorders in physicians are a meaningful cause of medical errors or preventable adverse events [ 4 , 5 ]. On the basis of empirical research, male sex appears to be a better predictor of poor performance or subsequent professional discipline than the presence of a mental disorder [ 6 12 ]. Therefore, it is not entirely clear why these policies have persisted and continue to encourage more referrals to PHPs.…”
Section: Introductionmentioning
confidence: 99%